Investigating the attenuated psychosis syndrome in youth with autism spectrum disorder: results from an observational study - Riccioni, Assia; Pontillo, Maria; Gialloreti, Lenardo Emberti; Cicala, Mariagrazia; Vasta, Michelangelo; Gatto, Mattia; Arturi, Lucrezia; Siracusano, Martina; Di Luzio, Michelangelo; Vicari, Stefano; Mazzone, Luigi (Frontiers in Psychiatry, 2025)
IntroductionDespite evidence suggesting increased rates of psychosis in individuals with autism spectrum disorder (ASD), the detection of prodromal psychotic symptoms, including attenuated psychosis syndrome (APS), remains underexplored in this population.MethodsThe primary aim of the present study was to characterize the clinical phenotype of young individuals with ASD who also present with APS (ASD/APS; n = 48) in comparison with individuals with APS only (n = 93) and those with ASD only (n = 30) (age range 9–23 years). Assessments included standardized measures of autistic symptoms (Autism Diagnostic Observation Schedule–Second Edition; ADOS-2), pre-psychotic symptoms (Structured Interview for Psychosis-Risk Syndromes; SIPS), and cognitive and adaptive functioning.ResultsOverall, the ASD/APS group demonstrated significantly poorer general adaptive skills compared with the APS group (p = 0.006) and the ASD group (p = 0.005). Compared with the APS group, the ASD/APS group exhibited lower scores across all SIPS domains, with the exception of SIPS-P1 (unusual thought content/delusional ideas; p = 0.062; t = −1.882; F = 5.44) and SIPS-P3 (grandiosity; p = 0.156; t = −1.435; F = 22.6). In contrast, the ASD/APS group displayed significantly higher scores in the repetitive and restricted behavior domain compared with the ASD group (p < 0.001). Notably, there were no significant differences in the age of APS onset across groups (p = 0.601; t = 0.525; F = 0.253).DiscussionThese findings provide a more nuanced characterization of APS features in individuals with ASD and emphasize the importance of screening for APS in this population, particularly those considered at increased risk. Early detection and intervention could facilitate timely therapeutic support, potentially improving long-term outcomes for these individuals.